CLINICAL, HEMATOLOGICAL, AND SEMINAL ALTERATIONS AND PARASITEMIA OF MALE GOATS EXPERIMENTALLY INFECTED WITH Toxoplasma gondii - Santana, Luís Fernando; Gaspar, Roberta Cordeiro; Rossi, Gabriel Augusto Marques; Nascentes, Gabriel Antônio Nogueira; Rodrigues, Eliana Aparecida; Oliveira, Gilson Pereira De; Costa, Alvimar José Da (Universidade Federal de Goiás, 2015)
Abstract:Toxoplasmosis is a parasitic disease that affects reproductive performance in small ruminants. Although the Toxoplasma gondii life cycle is well understood since 1960s, several aspects related to its infection remains unclear. This study aimed to determine the effects of T. gondiiexperimental infection, and the influence on clinical, hematological, parasitemia and seminal parameters in male goats. Nine animals were selected and distributed in three groups: GI (n=3) – control group (placebo) orally inoculated with saline solution; GII (n=3) – subcutaneously inoculated with 1 x 106 tachyzoites of T. gondii; and GIII (n=3) – orally inoculated with 2 x 105 oocysts of T. gondii. After that, clinical exams, serological tests, hemograms, parasitemia determination and semen evaluation were performed. Reciprocal serological titers had highest values of 4096 in both groups of goats infected with T. gondii,confirming the experimental infections. However, we could not observe clinical changes (except for mild hyperthermia on the 5th DAI in one of the animals - GIII) or in hematimetric parameters. Although there were some statistically significant changes (P <0.05) on the percentages of pathology and sperm concentrations in some of the dates between the infected and control animals, these changes were not associated with toxoplasmic infection. Infection was associated with animal handling methods and environmental factors.

Resumo:A toxoplasmose é uma enfermidade parasitária que afeta o desempenho reprodutivo de pequenos ruminantes. Apesar de o ciclo de vida do Toxoplasma gondiiser bem conhecido desde 1960, alguns aspectos relacionados com a infecção permanecem obscuros. Este estudo objetivou determinar os efeitos da infecção experimental por T. gondii e a influência sobre parâmetros clínicos, hematológicos, parasitêmicos e seminais de machos da espécie caprina. Nove animais foram selecionados e distribuídos em três grupos: GI (n=3) – grupo controle (placebo) oralmente inoculados com solução salina; GII (n=3) – subcutaneamente inoculados com 1 x 106 taquizoítos de T. gondii; e GIII (n=3) – oralmente inoculados com 2 x 105 oocistos de T. gondii. Posteriormente, foram realizados exames clínicos, testes sorológicos, hemogramas, determinação de parasitemia e avaliação seminal. Em ambos os grupos infectados com o parasita, a maior titulação sorológica observada foi 4096, confirmando a ocorrência da infecção. Entretanto, não foram observadas alterações clínicas (exceto por hipertermia no 5º DPI em um dos animais - GIII) ou nos parâmetros hematológicos. Apesar de ocorrer diferença estatística significativa (P <0,05) na porcentagem de patologias e concentração espermática em algumas datas entre os animais controle e infectados, essas alterações não foram associadas ao parasitismo, mas a fatores ambientais e de manejo dos animais.
ALTERAÇÕES CLÍNICAS, HEMATOLÓGICAS, SEMINAIS E PARASITEMIA DE CAPRINOS MACHOS EXPERIMENTALMENTE INFECTADOS COM Toxoplasma gondii
Keywords: experimental infection; IFI; reproductive diseases; small ruminant; toxoplasmosis; enfermidades reprodutivas; infecção experimental; pequenos ruminantes; RIFI; toxoplasmose